Armenia's Future, Relations with Turkey, and the Karabagh Conflict - Ter-Petrossian, Levon (Springer International Publishing, 2018)
This project addresses recurring questions about Armenian-Turkish relations, the legacy of the Armenian genocide of 1915, and relations between the Armenian diaspora and the Republic of Armenia. Additionally, it discusses the ongoing conflict with Azerbaijan, and the Armenian government's handling of the commemoration of the one-hundredth anniversary of the Armenian genocide.